International Women's Year Rally, London, 1975 (1975)
1975 1960-2000 "International Women's Year Rally, London, 1975" [EP0011b], 1975 This photograph shows members of the printing union, the Society of Graphical and Allied Trades, walking with an equal pay banner at the TUC International Women's Year Rally in London on 25 May, 1975. There was a meeting in Hyde Park followed by a march to Trafalgar Square.